A study on the economic using of steel slag aggregate in asphalt mixtures reinforced by aramid fiber - Alnadish, Adham; Aman, Mohd. Yusri (Asian Research Publishing Network (ARPN), 2018)
Due to the urgent need to conserve natural resources, the researchers have been focused on using plant wastes as an alternative source of natural resources. On the other hand, increasing costs of material and rising consumption of natural resources prompted engineers and researchers to look for other materials to enhance asphalt mixture performance, thus minimizing maintenance and rehabilitation of roads as well as saving costs. In this regard, steel slag aggregate is a by product of steel manufacturing, and it is considered as one of the well-known plant wastes, which is suitable for pavements applications. Although it is useful in terms of improving the performances of asphalt mixtures, it has also disadvantages such as expansion volume and high density. However, fibers could be described as a distinct material in the enhancement of asphalt mixture. This study is aimed to evaluate electric arc furnace (EAF) steel slag aggregate replaced natural coarse aggregate in the asphalt mixture reinforced by aramid fiber in order to reduce asphalt layer thickness, and hence reduce transportation costs resulting from high density of the steel slag aggregate. In addition, steel slag aggregate was immersed in the water for 6 months in order to minimize free lime and free magnesia content, which leads to the expansion volume. Six mixtures with different proportion of aramid fiber by total weight of the aggregate were evaluated. Mix1, Mix2, Mix3, Mix4, Mix5 and Mix6 corresponding to 100% of granite aggregate, coarse steel slag aggregate, coarse steel slag and 0.025% aramid fiber, coarse steel slag and 0.05% aramid fiber, coarse steel slag and 0.1% aramid fiber and coarse steel slag aggregate and 0.3 aramid fiber, respectively. However, the fine granite aggregate kept fixed for all mixtures. Thermogravimetric and XRD tests were used to evaluate the benefit of treatment steel slag aggregate while resilient modulus and dynamic creep were the performed tests of the mixtures. Response surface Methodology (RSM) using design expert6 was used to analyze results obtained in order to investigate the interaction between factor and responses of the dynamic creep. Mechanistic empirical pavement design approach was used to examine the possibility of extend service life or reducing thickness of asphalt layer as well as to assess the benefit of ultra-thin asphalt overlay containing steel slag aggregate and aramid fiber in terms of improving service life of existing asphalt layer. The results indicated that method of treatment steel slag was successful in reducing free lime and free magnesia content. Introducing aramid fiber by 0.05% to the total weight of the aggregate into mixture significantly increased resilient modulus and dynamic creep compared to the other mixtures, and it was the optimum content. The results of Mechanistic empirical pavement design indicated that Mix4 have significantly reduced asphalt layer thickness by around 20% if the service life kept constant, or increased service life by 1.24 if the thickness kept constant. In addition, ultra-thin asphalt layer overlay with Mix4 dramatically improved service life of existing asphalt layer.